1998
DOI: 10.2105/ajph.88.3.487
|View full text |Cite
|
Sign up to set email alerts
|

A regression analysis estimating the number of drug-using arrestees in 185 US cities.

Abstract: OBJECTIVES: This study sought to provide population-based estimates of drug-using arrestees in the 185 largest US cities. METHODS: A prevalence model for drug-using arrestees was developed by relating selected social indicators (from 1990 census data) and drug use rates (from Drug Use Forecasting program data) via logistic regression analysis. RESULTS: It was estimated that in 1990, across the 185 cities, about 925,000 arrestees used cocaine, 317,000 used opiates, 213,000 used amphetamines, 389,000 were drug i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Substance-abusing Latinas report higher involvement with the criminal justice system than their non-Latino White counterparts (Amaro et al, 2005, 2006; Wyatt et al, 2002). Examining heroin addicts in methadone maintenance in Southern California, Hser, Prendergast, Anglin, Chen, & Hsieh (1998) found that Latinas had more pretreatment involvement in the criminal justice system than non-Latino White women.…”
Section: Institutional Determinantsmentioning
confidence: 99%
“…Substance-abusing Latinas report higher involvement with the criminal justice system than their non-Latino White counterparts (Amaro et al, 2005, 2006; Wyatt et al, 2002). Examining heroin addicts in methadone maintenance in Southern California, Hser, Prendergast, Anglin, Chen, & Hsieh (1998) found that Latinas had more pretreatment involvement in the criminal justice system than non-Latino White women.…”
Section: Institutional Determinantsmentioning
confidence: 99%
“…Indirect estimation techniques tend to build upon existing data and their mutual relationship in order to estimate the number of non-observed cases in a given population. The latter include capture-recapture techniques [1,2,3,4,5,6,7,8], benchmark-multiplier methods [1,9,10,11], the truncated Poisson method [1,12,13], and the multivariate indicator method [14,15,16,17,18,19]. However, none of currently known methods is considered to be the gold standard since they all rely on a series of assumptions and limitations [20].…”
Section: Introductionmentioning
confidence: 99%